PYRUVATE KINASE ISOENZYMES FROM SUBMAXILLARY AND SUBLINGUAL SALIVARY GLANDS OF RAT (Rattus rattus norvaegicus, Berkenhout). I PURIFICATION AND PHYSICOCHEMICAL PROPERTIES - ROSA, CLAUDETE D.; OCAMPOS, DARIO; SASSAKI, KIKUE T.; CERQUEIRA-CESAR, MARCELO; ROSA, RUBENS (Archives of Veterinary Science, 1998)
Piruvatoquinase de glândula salivar submaxilar e sublingual de rato (Rattus rattus norvaegicus, Berkenhout) foi purificada até homogeneidade por salting out por precipitação com sulfato de amônio seguida de cromatografia de coluna, primeiro com fosfocelulose e eluição com solução 0,5M de KCl e depois com Blue Sepharose CL-6B eluida com PEP 5mM e ADP 5mM. Obteve-se atividade específica final de 324,5 UI/mg com rendimento global de 20,1% para SM-PK e de 427,4 UI com rendimento global de 9,5% para SL-PK, com pesos moleculares de 60.500 e 50.000 Daltons determinado em eletroforese do tipo PAGE com e sem SDS, para SM-PK e de 242.000 e 200.000 para SL-PK, sugerindo, com isso que se tratam de homotetrâmeros. Por eletroforese em gel de acetato demonstrou-se que tanto SM-K como SL-K possuem somente uma forma isoenzimática com mobilidade eletroforética similar à PK tipo L de fígado de rato e do tipo M2 do rim de rato. verificou-se que o pH ótimo para ambas as enzimas é de 7,4. Abstract Pyruvate kinase from rat (Rattus rattus norvaegicus) submaxillary and sublingual salivary glands was purified to homogeneity by a 3-step process. One step involved salting out by ammonium sulfate precipitation and two steps, column chromatography, first with phosphocellulose and elution with 0.5M KCl and then with Blue Sepharose CL-6B eluted with 5mM PEP and 5 mM ADP. The final specific activity of SM-PK was 324.5 IU/mg with an overall yield of 20.1%. The values for SL-PK were 427. 4 IU/mg and a yield of 9.5%. The molecular weights of the native enzymes and their subunits, as determined by PAGE electrophoresis with or without SDS were 60.500 and 50.000 Daltons respectively, for SM-PK and 242.000 and 200.000 for SL-PK, suggesting that these enzymes were present as homotetramers. By means of cellulose acetate electrophoresis it has been demonstrated that both SM-PK and SL-PK possess only one isozymic form displaying eletrophoretic mobility similar to that of the L-type PK from rat liver and M2- type PK form rat kidney. Optimum pH for both SM-PK and SL-PK was found to be 7. 4 in Tris-HCl buffer.